Understanding suicidal ideation in psychosis: findings from the Psychological Prevention of Relapse in Psychosis (PRP) trial. - Fialko, L; Freeman, D; Bebbington, P; Kuipers, E; Garety, P; Dunn, G; Fowler, D (2006)
OBJECTIVE: To examine the clinically important phenomenon of suicidal ideation in psychosis in relation to affective processes and the multidimensional nature of hallucinations and delusions. METHOD: In a cross-sectional study of 290 individuals with psychosis, the associations between level of suicidal ideation, affective processes, positive symptoms, clinical and demographic variables were examined. RESULTS: Forty-one per cent of participants expressed current suicidal ideation. Suicidal ideation was associated with depressed mood, anxiety, low self-esteem, negative illness perceptions, negative evaluative beliefs about the self and others and daily alcohol consumption. Frequency of auditory hallucinations and preoccupation with delusions were not associated with suicidal ideation; however, positive symptom distress did relate to suicidal thoughts. CONCLUSION: Affective dysfunction, including distress in response to hallucinations and delusions, was a key factor associated with suicidal ideation in individuals with psychotic relapse. Suicidal ideation in psychosis appears to be an understandable, mood-driven process, rather than being of irrational or 'psychotic' origin.